THE EFFECT OF 9P AND BRAND IMAGE ON LOYALTY USING THE STRUCTURAL EQUATION MODELLING (SEM) METHOD OF PLS AND SATISFACTION BECOMES AN INTERVENING VARIABLE - Elpawati Elpawati; Puspi Eko Wiranthi; Puji Rahmawati (Syarif Hidayatullah State Islamic University Jakarta, 2021)
This study was conducted to determine and analyze the level of satisfaction and loyalty of Oppa Galbi Lebak Bulus restaurants and the influence of marketing mix and brand image on consumer satisfaction and loyalty. This study used primary data and secondary data. The primary data in the study is data taken based on consumer responses and the results of direct interviews with the owner. Secondary data from this study were obtained from previous studies, that is, the literature is related to related research. The sampling technique in this study was purposive sampling with a total of 100 respondents. The analytical tool used is Structural Equation Modelling (SEM)- (PLS). The results of this study showed the average level of satisfaction, the highest value was in the willingness to recommend sub-variable which had a value of 4.09 in the satisfied category. The results of the calculation of the average loyalty level of the highest value are found in the sub-variable which reflects having a value of 4.17 in the loyal category. The results of this study show that the variables of the marketing mix and brand image towards satisfaction and loyalty have a significant effect.